Developing Bilingual Collection Labels at Museum Gubug Wayang - Miftakhul Jannah (Jurnal Linguistik Terapan, 2021)
Museum Gubug Wayang stands as the sole museum in Mojokerto City, boasting an array of collections ranging from Wayang and Traditional Heirloom to Si Unyil's Puppet, Artefact Mojopahit, and Batik Nusantara. The museum attracts a diverse range of visitors, including both local and international tourists. However, an issue arose as the collections' labels were exclusively printed in Indonesian, posing difficulties for foreign tourists to comprehend the displays effectively. To address this, the museum sought to develop bilingual labelling in both Indonesian and English for their collections.  The research adopted a qualitative approach, utilizing the DDR (Design and Development Research) method, with Museum Gubug Wayang Mojokerto serving as the setting. The study successfully resulted in bilingual labels placed beneath the museum's collections. Respondents confirmed that these labels were easy to comprehend and greatly aided them in obtaining information about the exhibits at the museum.